1985
DOI: 10.3758/bf03329842
|View full text |Cite
|
Sign up to set email alerts
|

Conditional discrimination learning by pigeons: The role of training paradigms

Abstract: Three groups of pigeons (n = 8) learned a successive discrimination, 538-nm S+ versus 576-nm S-, in one context, say , houselight and tone, and the reversal in another context, say , dark and noise. In Group 1, the single reversal paradigm was used ; for Group 2, the problems alternated daily; and for Group 3, they alternated minute by minute. Wavelength generalization gradients obtained in both contexts revealed conditional control by context, which was weakest in Group 3.Conditional discrimination learning r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
(14 reference statements)
3
10
1
Order By: Relevance
“…Honey and Watt (1999) found acquisition of differential responding with contextual cues that signaled the reinforcement and nonreinforcement of X and Y to be faster than that in an earlier experiment in which discrete cues were used (Honey & Watt, 1998). Thomas and Goldberg (1985) found better discriminative performance in pigeons with a daily alternation procedure in which reinforced trials with one target and nonreinforced trials with the other target (e.g., AϪXϩ and AϪYϪ) occurred on one day and the reverse reinforcement contingencies (e.g., BϪXϪ and BϪYϩ) operated on a different day than with the conventional training schedule in which all trial types are mixed within a session. Finally, Trapold (1970) obtained superior discriminative performance on an instrumental biconditional discrimination when one food outcome was used for reinforcing one response and a different food outcome was used to reinforce the other response.…”
Section: Results and Discussion Biconditional Discrimination Trainingmentioning
confidence: 83%
See 1 more Smart Citation
“…Honey and Watt (1999) found acquisition of differential responding with contextual cues that signaled the reinforcement and nonreinforcement of X and Y to be faster than that in an earlier experiment in which discrete cues were used (Honey & Watt, 1998). Thomas and Goldberg (1985) found better discriminative performance in pigeons with a daily alternation procedure in which reinforced trials with one target and nonreinforced trials with the other target (e.g., AϪXϩ and AϪYϪ) occurred on one day and the reverse reinforcement contingencies (e.g., BϪXϪ and BϪYϩ) operated on a different day than with the conventional training schedule in which all trial types are mixed within a session. Finally, Trapold (1970) obtained superior discriminative performance on an instrumental biconditional discrimination when one food outcome was used for reinforcing one response and a different food outcome was used to reinforce the other response.…”
Section: Results and Discussion Biconditional Discrimination Trainingmentioning
confidence: 83%
“…A number of studies have shown successful performance on Pavlovian and instrumental biconditional discriminations in several species, including bees (Schubert, Lachnit, Francucci, & Giurfa, 2002), rabbits (Saavedra, 1975), rats (Colwill & Delamater, 1995;Honey & Watt, 1999;Preston, Dickinson, & Mackintosh, 1986;Trapold, 1970), and pigeons (Looney, Cohen, Brady, & Cohen, 1977;Thomas & Goldberg, 1985). To our knowledge, however, there have been no studies of biconditional discrimination learning in the mouse.…”
Section: Methodsmentioning
confidence: 87%
“…The present experiments revealed that CSDR training was necessary for floor tilt and texture to gain conditional control. Yet Thomas and Goldberg (1985) directly compared single-reversal and CSDR procedures in an experiment with houselight conditional cues and key color discriminative cues and found equal (and excellent) conditional control with both procedures. A third group in their experiment, exposed to all four combinations of houselight and key color conditions on a minute-by-minute basis within sessions, performed more poorly.…”
Section: Resultsmentioning
confidence: 99%
“…The acquisition of contextual control of the F-P and the F-N discriminations in 2 birds (All and F33) after separate training on the two discriminations suggests that the within-session trial-by-trial alternation of contexts that had been used in the original training might have produced interference between trials and prevented the establishment of contextual control (see Thomas, Cook, & Terrons, 1990;Thomas & Goldberg, 1985). However, the 3rd bird (HI2) failed even with separate training on the two discriminations, and the F-N discrimination of F33 was improved after the original within-session trial-bytrial alternation method was rearranged.…”
Section: H12mentioning
confidence: 99%
“…The stimulus controlling these three-term contingencies was the contextual cue of the houselight. Several operant discrimination studies show that this cue is able to acquire the conditional stimulus function (e.g., Thomas & Cur-ran, 1988;Thomas, Curran, & Russell, 1988;Thomas & Goldberg, 1985;Thomas, McKelvie, & Mah, 1985;Thomas & Schmidt, 1989).…”
mentioning
confidence: 99%